PELATIHAN REGULASI EMOSI DENGAN MEDIA “EMOTIONAL ACTIVITIES” PADA ANAK BERKEBUTUHAN KHUSUS - Rahmah Saniatuzzulfa; Kurniasih Ayu Archentari (Jurnal Psikohumanika, 2023)
Emotional regulation skills should be taught to Children with Special Needs in order to provide appropriate responses to various situations. The learning methods used by Children with Special Needs focus on communication, direct instruction, and cooperative learning. This study aims to train the ability to regulate emotions in Children with Special Needs with a medium that attracts Children with Special Needs, namely Emotional Activities. Emotional Activities consists of picture storybooks, boardgames, activity sheets and videos. The measurement instrument uses The Emotion Regulation Questionnaire (ERQ) with cognitive reappraisal reliability of α = 0.910 and expressive suppression of α = 0.658. This study used a quasi-experimental method with one group pretest-posttest design. Children with Special Needs respondents totaled 18 people. The validation results of SME (Subject Matter Experts) show that Emotional Activities have included the goals to be achieved. Data analysis to test the effectiveness of Emotional Activities using Wilcoxon yielded p=0.043 (p<0,05). Conclusion of this research that Emotional Activities can train emotional regulation skills in Children with Special Needs.